In vitro cytotoxicity and virucidal efficacy of potassium hydrogen peroxymonosulfate compared to quaternary ammonium compound under various concentrations, exposure times and temperatures against African swine fever virus - Watcharee Sovijit (Veterinary World, 2021)
Background and Aim: The selection and proper application of disinfectants are crucial to the prevention of many diseases, so disinfectants must be evaluated before being used for the prevention of African swine fever (ASF). Three disinfectant products belonging to the group of potassium hydrogen peroxymonosulfates, product A and product B, and a quaternary ammonium compound called product C, were examined in vitro for host cell cytotoxicity and the efficacy of ASF virus inactivation. The study parameters included various concentrations, exposure times, temperatures, and degrees of cytotoxicity.